The Role of Nadzir in Resolving Waqf Land Disputes - Alam, Nur; Salmawati, Salmawati; Zainuddin, Zainuddin (Golden Ratio of Law and Social Policy Review, 2024)
This study aims to determine and analyze the factors that cause waqf land disputes and to know and analyze the role of nadzir in defending the land, in the event of a waqf land dispute. This study uses the empirical method or directly down to the field. The location of the research was carried out at the Luwu Grand Mosque, Palopo City and North Wara KUA. The types and sources of data used are primary data and secondary data with data collection techniques obtained through interviews and literature study. The number of samples as many as 3 people, namely a Nadzir, community leaders and the Head of KUA. The data obtained were processed by qualitative analysis with a deductive approach. The results showed that Nadzir's role in defending the land, in the event of a waqf land dispute, was to protect and supervise what was entrusted to him by representing the waqf land object when sued both inside and outside the court, showing evidence of land waqf , and seeking to resolve the dispute. by deliberation. The factors that cause waqf land disputes include the lack of good communication, the absence of a waqf pledge deed, the heirs suing the waqf land, the increasingly strategic location of the land, the land object does not have legal certainty, and the endowment with a deed below. hand. The research recommendation is nadzir in an effort to defend the land, if there is a dispute over waqf land, that is, play an active role in trying to make the problem resolved by deliberation. It is resolved by deliberation will be much more effective and the disputing parties do not feel disadvantaged but the parties will feel mutually won. There are also people in general who want to endow their land, they should educate themselves or seek information related to land waqf procedures to the authorized official before waqf of land. As well as in implementing the transfer of waqf from wakif to nadzir, the legal position of the nadzir when receiving the waqf land object must be clear.